The comparative effect of propolis in two different vehicles; mouthwash and chewing-gum on plaque accumulation and gingival inflammation - Ercan, Nuray; Erdemir, Ebru Olgun; Ozkan, Serdar Yucel; Hendek, Meltem Karsiyaka (European Journal of Dentistry, 2015)
Objective: In general, chemical plaque agents have been used in mouthwashes, gels, and dentifrices. In some situations, application of mouthwashes and dentifrices can be difficult. Therefore, different approaches for oral health-care have been needed. The aim of this study was to evaluate the effect of propolis chewing-gum compared to propolis-containing mouthwash on gingival inflammation and plaque accumulation on patients that refrained from daily oral hygiene procedures for 5 days. Materials and Methods: 10 college students with systemically healthy and very good oral hygiene and gingival health were included in this randomized, single-blind, crossover 5-day plaque regrowth with a 3-day washout period clinical study. After plaque scores were reduced to zero, participants were asked to refrain from oral hygiene procedures and allocated to either propolis mouthwash or chewing-gum group. Chewing-gum was performed after meals 3 times a day for 20 min mouthwash group was instructed to rinse mouthwash 2 times a day for 1 min. On day 5, the clinical periodontal measurements containing plaque and gingival indexes were taken from the participants. Results: The both plaque and gingival indexes of propolis mouthwash group were significantly lower than that of the propolis chewing-gum group (P = 0.005). Conclusion: It was demonstrated that the propolis mouthwash was more effective than the propolis chewing gum on the plaque inhibition and the gingival inflammation.
Keywords: Chewing gum; dental plaque; gingival inflammation; mouthwashes; propolis